STOCK ASSESSMENT OF SIN CROAKER JOHNIEOPS SINA (CUVIER) FROM BOMBAY WATERS - CHARKABORTY, SUSHANT KUMAR (Journal of Indian Fisheries Association, 2015)
Growth, mortality and stock parameters of Johnieops sina Â·(Cuvier) based on the data collected from 1989 to 1994 from Sassoon Dock and New Ferry Wharf landing centres of Greater Bombay has been discussed here. The von Bertallanffy’s growth parameters for this species were estimated as follows, Loo = 266 mm, K = 0.91 per year and Woo= 193 g. This species grows to 159 and 223 mm at the end of first and second year of its life. The mortality parameters estimated were Z = 6.17, M = 2/’3 and F = 4.14. TheE and U were calculated as 0.62 and 0.63 respectively. Length cohort and Thompson Bell analyses show that there is no decline in the catches at the present level of fishing. But even by doubling the efforts the catches can go up by only 9.4 % indicating that the fishing efforts is not economical and proportional to the increase in yield.